PENGARUH KUALITAS LAYANAN DAN HARGA KARTU SELULER TELKOMSEL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PENGGUNA KARTU HALO DI BANJARMASIN (Studi Pada Kantor Grapari Telkomsel Kota Banjarmasin) - Nandawan Nizardy; Hairudinor Hairudinor; Setio Utomo (Lambung Mangkurat University, 2021)
This study aims to determine the effect of partially and simultaneously between Service Quality (X1) and Price (X2) on Purchasing Decisions (Y). The population in this study is consumers in the Banjarmasin Grapari office who use Halo cards for sampling techniques using non-probability sampling with a total sample of 140 people. Data collection techniques in this research is by distributing questionnaires. Data analysis techniques using Multiple Linear Regression Analysis. The results of the study prove that Service Quality (X1) partially has a significant positive effect on Purchasing Decisions (Y) of 18%. And Price (X2) partially has a significant positive effect on Purchasing Decisions (Y) with a large influence of 78.4%. The results of simultaneous testing show that service quality (X1) and price (X2) have a significant positive effect on purchasing decisions (Y) with a large effect of 78.8%. Keywords: Service Quality; Price; Purchase Decisions